2021
DOI: 10.1371/journal.pone.0250554
|View full text |Cite
|
Sign up to set email alerts
|

Levels and predictors of fear and health anxiety during the current outbreak of COVID-19 in immunocompromised and chronic disease patients in Saudi Arabia: A cross-sectional correlational study

Abstract: Coronavirus disease 2019 (COVID-19) infection has become a clinical threat to healthy people as well as immunocompromised patients and those with pre-existing chronic diseases around the world. This study, which used a cross-sectional correlational design, aimed to assess the levels of fear and health anxiety and to investigate their predictors during the current outbreak of COVID-19 in immunocompromised and chronic disease patients in Saudi Arabia. Sociodemographic and clinical data, fear of COVID-19, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
47
3
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 31 publications
(40 reference statements)
11
47
3
9
Order By: Relevance
“…This finding is contrary to the one that was reported by Padidar et al [85] but in agreement with that of Valenti and Faraci [46]. In accordance with some previous studies [82][83][84]86,87], willingness to take COVID-19 vaccines increased with educational levels. Additionally, male respondents had lower compliance indicators.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is contrary to the one that was reported by Padidar et al [85] but in agreement with that of Valenti and Faraci [46]. In accordance with some previous studies [82][83][84]86,87], willingness to take COVID-19 vaccines increased with educational levels. Additionally, male respondents had lower compliance indicators.…”
Section: Discussionsupporting
confidence: 79%
“…The results further showed that anxiety and days with feelings of depression increased the two compliance indicators. The feelings of anxiety can be related to expression of fear in the context of unfolding events during the COVID-19 pandemic [86,87]. Additionally, the number of days with nervous feelings decreased the probability of willingness to take COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…This finding appeared higher than the previous result among nonpregnant subjects during this pandemic. 44 Primiparous women had significantly higher mean scores than multiparous mothers. There was a previous supportive finding in which primiparous mothers had reported higher worries than their counterparts.…”
Section: Discussionmentioning
confidence: 86%
“…4,14 However, the majority of participants in our study reported that they would hold information from the Ministry of Health and WHO with high regard a finding consistent with that of Kwok et al 29 and Alotiby et al 14 In this respect, policymakers and health workers could use this opportunity to disseminate the right information to the public regarding the safe use of herbal remedies. 30 The current study revealed a mean FCV-19S score of 21.7 (SD=5.9, median=21). This was higher than reported in similar studies done in Eastern Europe (mean=17.2, median=17) and Japan (median=16.67) as well as in other countries like New Zealand, Spain, Russia, Israel, and Pakistan, where the mean scores were distributed between 15 and 19 points.…”
Section: Discussionmentioning
confidence: 49%
“… 4 , 14 However, the majority of participants in our study reported that they would hold information from the Ministry of Health and WHO with high regard a finding consistent with that of Kwok et al 29 and Alotiby et al 14 In this respect, policymakers and health workers could use this opportunity to disseminate the right information to the public regarding the safe use of herbal remedies. 30 …”
Section: Discussionmentioning
confidence: 99%